1995
DOI: 10.1128/aac.39.2.290
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal pirodavir (R77,975) treatment of rhinovirus colds

Abstract: A randomized, double-blind, placebo-controlled trial assessed the therapeutic efficacy of intranasal pirodavir in naturally occurring rhinovirus colds. Adults with symptoms of Յ2 days' duration were randomly assigned to intranasal sprays of pirodavir (2 mg per treatment) or placebo six times daily for 5 days. In people with laboratory-documented rhinovirus colds (53 in the pirodavir group, 55 in the placebo group), no significant differences in the resolution of respiratory symptoms were apparent between the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
53
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(54 citation statements)
references
References 10 publications
1
53
0
Order By: Relevance
“…14 While effective in experimental challenge studies when administered very frequently intranasally, 15,16 the ester functionality of pirodavir 2 has been shown to undergo facile hydrolysis in vivo to the carboxylic acid, which is inactive, 17 and this ease of hydrolysis renders the molecule unsuitable for oral administration.…”
mentioning
confidence: 99%
“…14 While effective in experimental challenge studies when administered very frequently intranasally, 15,16 the ester functionality of pirodavir 2 has been shown to undergo facile hydrolysis in vivo to the carboxylic acid, which is inactive, 17 and this ease of hydrolysis renders the molecule unsuitable for oral administration.…”
mentioning
confidence: 99%
“…The HEV include over 70 viruses that are associated with diverse clinical syndromes ranging from mild, self-limiting infections to fulminant and potentially fatal disease (3,52,53). Earlier clinical studies with agents that inhibit virus attachment and/or uncoating (e.g., tremacamra, a soluble intracellular adhesion molecule-1, pirodavir, and pleconaril) and nonspecific antiviral agents such as ␣-2␤ interferon have demonstrated that prevention and early treatment of HRV colds could provide clinical benefit (3,(18)(19)(20)(21)(22)(23)53). Recently, a retrospective analysis of two multicenter clinical trials demonstrated that pleconaril, a capsid-function inhibitor (17), significantly reduced the duration and severity of picornavirus-induced colds (24).…”
mentioning
confidence: 99%
“…These include Rupintrivir, 5 a viral 3C protease inhibitor, and a number of compounds that prevent virus entry into cells by binding to the viral capsid: Pirodavir, 6 Pleconaril, 7 and BTA798. 8 Only the latter of these is currently in clinical development, the others having been terminated due to lack of clinical efficacy or unacceptable side effects.…”
mentioning
confidence: 99%